Religious Culture Based Character Learning Management in MIN 1 Malang and MIN 2 Malang - Dzaqi Hijrotin; Sofyan Tsauri; Abd. Muis (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Character education is one of the main focuses of national education that requires systematic management so that character values can be internalized in students' behavior. In the context of madrasas, religious culture is a strategic instrument to support character formation through various learning and habituation activities. However, the success of character education is largely determined by the effectiveness of the learning management applied. This study aims to analyze the management of religious culture-based character learning in MIN 1 Malang and MIN 2 Malang which includes aspects of planning, implementation, and evaluation. The research uses a qualitative approach with a multisite study design. Data were obtained through in-depth interviews, participatory observations, and documentation studies involving madrasah heads, deputy heads of curriculum, teachers, and students. Data analysis is carried out through data condensation, data presentation, and conclusion drawing with cross-site analysis techniques. The results of the study show that character learning planning is carried out in an integrated manner with the vision and mission of the madrasah, curriculum, religious culture programs, and the organization of supporting resources. The implementation of character learning is realized through the integration of character values in learning, habituation of religious culture, teacher example, and continuous coordination. MIN 1 Malang implements a coordination pattern based on the leadership of madrasah heads, while MIN 2 Malang develops systemic patterns through special teams and strengthening institutional religious culture. Evaluation is carried out on an ongoing basis through supervision, program monitoring, and assessment of student character development. The findings of the study confirm that the integration of management functions and religious culture is the main factor in the success of the formation of students' character in madrasah.